Hubungan dinamik antara inflasi kemeruapan inflasi dan pertumbuhan output: Bukti empirikal di Malaysia - Mohd Nor, Abu Hassan Shaari; Tan, Yan Ling (Universiti Utara Malaysia, 2009)
Purpose – The main purpose of this study was to analyse the dynamic relationship between inflation, inflation uncertainty and output growth in Malaysia for the period 1980 to 2004. Design/Methodology/Approach – The EGARCH model was used to estimate the infl ation uncertainty and the Vector Autoregressive (VAR) technique, which includes the Granger causality test, was employed in the investigation of dynamic relationships between these variables. Findings – There was significant evidence on the existence of one way positive relationships between inflation and inflation uncertainty in Malaysia. Further investigation showed that a high inflation level tends to have a negative effect on output growth. However, there was no significant evidence on the relationship between inflation uncertainty and output growth. Originality/Value – This paper explores the time varying volatility of inflation in Malaysia and investigates the dynamic relationship between inflation, inflation uncertainty, and output growth.